Cases of tuberculosis coinfected with HIV in a state in the Brazilian Northeast - Marques, Cristiane da Câmara (2019)
The objective of this study was to characterize the reported cases of Tuberculosis coinfected with the Acquired Immunodeficiency Virus in Rio Grande do Norte, state of northeastern Brazil. This is an ecological, retrospective study based on notification data from the Notification Grievance Information System between 2001 and 2015. The data were presented in graphs, images and tables and analyzed from current studies on the subject. There was an increase in the number of cases during the period analyzed. Prevalence of confirmed male cases (75.28%), between 20 and 39 years old (55.63%), who had the pulmonary form of tuberculosis (71.62%), developed AIDS (91.27%) and entered the service in the new case situation (73.80%). A high amount of ignored data was observed, for example, the variables illicit drugs (88.82%) and smoking (89.52%). It is concluded that the findings indicate the increase in the number of coinfections and a concern for the completeness of the data during the notifications